2021
DOI: 10.1177/02537176211021789
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of COVID-19 on Children and Adolescents: A Systematic Review

Abstract: Background and aims: The outbreak of COVID-19 led to a significant psychological impact on individuals, particularly those belonging to vulnerable groups. This study aimed to synthesize literature on the psychological impact of COVID-19 among children and adolescents. Methods: Electronic search engines were used to identify studies till March 2021 that reported symptoms of psychological origin in children and adolescents. Information was extracted using a predefined template, and qualitative analysis was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 46 publications
2
96
0
6
Order By: Relevance
“…Among the broader population, social distancing measures and school closures can also impact children's mental health. In a previous review, anxiety and depression were reported as the most prevalent psychological symptoms in children and adolescents during the COVID-19 pandemic ( 11 ). For example, a study in Wuhan, Hubei province, China, reported that depressive and anxiety symptoms affected 22.6 and 18.9% of primary students, respectively ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the broader population, social distancing measures and school closures can also impact children's mental health. In a previous review, anxiety and depression were reported as the most prevalent psychological symptoms in children and adolescents during the COVID-19 pandemic ( 11 ). For example, a study in Wuhan, Hubei province, China, reported that depressive and anxiety symptoms affected 22.6 and 18.9% of primary students, respectively ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, the clinical and semiological characteristics of patients with FS were similar between patients who were diagnosed before the pandemic compared with those who received the diagnosis during the pandemic. Therefore, we can conclude that while this deadly outbreak has caused significant stress for everyone [9] , [10] , [11] , [12] , it has not affected the characteristics of FS significantly.…”
Section: Discussionmentioning
confidence: 81%
“…This virus is highly contagious and has a high potential for person to person transmission. This deadly outbreak has caused more than five million deaths, massive job losses, various psychiatric problems, and increasing numbers of relationship difficulties worldwide (all of which may be considered as potential precipitating factors for FS) [9] , [10] , [11] , [12] . Therefore, it is plausible to consider this pandemic as a potentially significant factor that may affect the characteristics of FS.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that a single type of natural disaster, or the COVID-19 pandemic, can cause psychological distress in adolescents, such as depression, anxiety, and stress [ 6 , 7 , 8 , 9 ]. The prevalence of psychological distress among adolescents ranges from 10% to 30% in Western and Eastern societies [ 10 ]. In addition to mental health, limited studies have explored the effects of psychological distress on adolescents’ cyber problem behaviors, such as cyberbullying during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%